Design and Investigation of the Mini-multilayer Inverse Conical Coil for Micro Displacement Detection in Fuel Injection Nozzles - Tatoglu, Akin; Campana, Claudio; Yu, Ying; Alnajjar, Hisham; Nazaryan, Nikolay (Journal of Vibration Testing and System Dynamics, 2026)
A fuel injector plays an important role in performance and emissions of diesel engines. Among other factors, the quantity of fuel injected into the combustion cylinder is dictated by the nozzle seat and sac geometry, spray hole size and K factor, and the needle lift. These factors can affect the timing of the needle closing, potential bounce and transverse motion of the needle. In order to optimize needle closing, the motion of the needle valve needs to be understood. For this purpose, a mini multilayer conical inductance coil was designed to measure needle valve motion as it is actuated in a nozzle body, with the nozzle being the core of the coil. This approach minimizes intrusion into the injector assembly which can pose a risk for leakage.